Subsupercritical Water Generated by Inductive Heating Inside Flow Reactors Facilitates the Claisen Rearrangement - Oltmanns, Mona; Kirschning, Andreas (Synlett, 2020)
Claisen rearrangement of electron-deficient O-allylated phenols, including fluorine-modified phenols, is facilitated in aqueous media at high temperatures and pressures under flow conditions, as opposed to organic solvents. The O-allylation of phenols can be coupled with the Claisen rearrangement in an integrated flow system.
Keywords: Claisen rearrangement; flow chemistry; fluorobenzenes; inductive heating; supercritical water